Otological surgery in paediatric photosensitive patients. (December 2018) - Bates, James; Hall, Andy; Kunanandam, Thushitha; Hewitt, Richard
Abstract: There are a wide range of genetic and auto-immune conditions where UV light exposure poses a threat of UV irradiation to the external auditory canal, tympanic membrane and surrounding skin. Preoperative Ultraviolet Light (UV) measurements were taken in the operating theatre with standard operating microscope and an approved UV light meter prior to surgery on a patient with xeroderma pigmentosa. UV light meter readings of UV index 75 were taken at an operating distance of 290mm. Proceeding with otological surgery with a high UV index would result in a significant UV radiation burn. Utilising a Dermagard and a specific UV filter applied to the microscope resulted in acceptable UV light readings. We highlight the potential morbidity of otological surgery in paediatric photosensitive conditions. We also recommend a management plan to avoid damage by UV radiation in photosensitive patients.